Peran Dewan Keamanan PBB dalam Penyelesaian Sengketa Internasional: Studi Kasus Konflik Timur Tengah - Fajriani, Rifa Aziza; Nurhalizah, Silvana Putri; Mardotillah, TB Sultan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The Middle East conflict is one of the longest and most complex conflicts in modern history, involving multiple countries and causing significant regional instability. This journal aims to analyze the role of the United Nations Security Council (UNSC) in resolving international disputes, with a special focus on conflicts in the Middle East. Using qualitative methods with a case study approach, this research examines various UNSC interventions through secondary data analysis from research reports, journal articles, books and other reliable sources. The research results show that the UNSC has broad powers and authority to resolve conflicts, including issuing resolutions, implementing sanctions, sending peacekeeping troops, and taking military action if necessary. However, the UNSC faces various obstacles such as the use of veto rights by permanent members, conflicting national interests, limited resources, and inconsistent compliance by member countries. In conclusion, although the UNSC plays a crucial role in maintaining international peace and security, its effectiveness in resolving conflicts is highly dependent on the cooperation and commitment of all UN member states.